Penatalaksanaan Holistik Pada Pasien Diare Akut Dehidrasi Ringan Sedang dan Gizi Buruk Melalui Pendekatan Kedokteran Keluarga - Firdha Yossi Chani; Diana Mayasari (CV. Jasa Sukses Abadi, 2020)
Nowadays, the high morbidity and mortality rates caused by diarrhea require prompt and precise initial management. Nutritional conditions are one of the causes of the high morbidity of diarrhea in children. Poor nutritional conditions will have an impact on disruption of growth, mental development and intelligence of children and increase the likelihood of infection in children. In this case family medicine approach needs to be done to identify risk factors and clinical problems in patients, as well as to conduct holistic and comprehensive management with the application of evidence based medicine family doctors through a patient centered approach and family approach. The study conducted was Case Report. Primary data were obtained through alloanamnesis and physical examination by making a home visit, and filling in patient files. Secondary data was taken from the patient's medical record. The assessment is based on an initial holistic diagnosis, process and end of visit. Based on the final holistic diagnostic An. V had acute diarrhea, some dehydration and malnutrition, internal and external risk factors were found. Patient weight is very low (malnutrition), lack of family knowledge of the illness suffered and lack of awareness of cleanliness and balanced nutrition are the main factors of the problem. The family is given intervention by medical treatment and counseling using leafleates. Then an evaluation a conclusion can be drawn that there is an increase in knowledge about disease, hygiene and balanced nutrition